Piping and pipeline calculations manual construction, design, fabrication, and examination - Ellenberger, J. Phillip
Piping and Pipeline Calculations Manual, Second Edition provides engineers and designers with a quick reference guide to calculations, codes, and standards applicable to piping systems. The book considers in one handy reference the multitude of pipes, flanges, supports, gaskets, bolts, valves, strainers, flexibles, and expansion joints that make up these often complex systems. It uses hundreds of calculations and examples based on the author's 40 years of experiences as both an engineer and instructor. Each example demonstrates how the code and standard has been correctly and incorrectly applied. Aside from advising on the intent of codes and standards, the book provides advice on compliance. Readers will come away with a clear understanding of how piping systems fail and what the code requires the designer, manufacturer, fabricator, supplier, erector, examiner, inspector, and owner to do to prevent such failures. The book enhances participants' understanding and application of the spirit of the code or standard and form a plan for compliance. The book covers American Water Works Association standards where they are applicable. Updates to major codes and standards such as ASME B31.1 and B31.12 New methods for calculating stress intensification factor (SIF) and seismic activities Risk-based analysis based on API 579, and B31-G Covers the Pipeline Safety Act and the creation of PhMSA.